A Perfect Fifth of Blue and Red: Enlightened Harmonies of the Senses - Barnet, Edward (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2019)
In this article, I use Louis-Bertrand Castel’s attempt to create a music of colours as a window into 18th-century debates on the inter-relationship between physics, physiology, and sense experience. In part one, I address Castel’s original 1725 proposition to build an “ocular harpsichord,” a musical instrument designed to play colour rather than sound. I argue that Castel’s idea relied in equal measure on contemporary music theory, optics, and neurophysiology. In part two, I examine Castel’s attempts to justify his new music experimentally. Though his purported demonstrations became more eclectic, the core theoretical principles behind his optical music remained the same. In part three, I turn to what should have been the triumph of Castel’s career: his creation of a partially functioning harpsichord in 1755, along with the publication of two proposals for other sensorial musics in 1753 and 1755. The ostensible failure of Castel’s idea points to the limitations — theoretical, experimental, aesthetic — of his original proposal. At the same time, their enduring power to inspire spoke to the appeal of music as an explanatory framework, encompassing both art and science, body and mind.